Urgensi Formulasi Perlindungan Hukum dan Kepastian Pidana terhadap Pengaturan Tindak Pidana Deepfake dalam Sistem Hukum Pidana Nasional - Yang Meliana (CV Rewang Rencang, 2025)
This research focuses on the emergence of deepfake crimes as a consequence of digital technological advancements, posing serious threats to privacy rights, reputation, and human dignity. The national criminal law system in Indonesia has yet to establish specific regulations addressing this offense, creating an urgent need for the formulation of new legal norms to ensure legal certainty. The study also highlights the inadequacy of legal protection for victims from the perspectives of justice and human rights. Utilizing a normative juridical method, this research finds that the current legal framework is insufficient to address the complexity of deepfake crimes. The findings suggest the necessity for a specific criminal law formulation and the application of a restorative justice approach to enhance victim protection and improve the effectiveness of criminal law enforcement.